Perception of Online Learning among STEM School Students: Prospects and Challenges - Bano, Khushnuda; Ahmad, Jasim (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2026)
The concept of education has been changed radically in the last few years due to covid -19 pandemic. During COVID-19 pandemic the whole world faced a major transformation in the educational system to emergency virtual classes. However, this situation creates an opportunity to evaluate the efficacy of online learning from students’ perspectives. This study aims at exploring the experiences of secondary level students during online learning. The paper intends to assess the challenges, opportunities and successes for online learning. To discover the challenges and opportunities for online learning, secondary level students from a STEM based school in Delhi was surveyed about their experiences of online classes. The sample was chosen using simple random sampling technique. The data was collected through a self-constructed tool. Data was analyzed using quantitative as well as qualitative techniques. The study reveals that despite various challenges like digital divide, poor ICT infrastructure, lack of interaction, time management, cyber safety related issues etc. The perception was positive towards online learning. However, the unequal distribution of digital technology and quality of education provided online is crucial. Findings suggests that there is scope for innovation in infrastructure and technology. Digital development should be focused. It also provides guidelines to the educationist and curriculum developer for designing flexible educational program and pedagogical reforms required for ensuring the good quality of online education. Online learning is now become an essential part of learning and a harmonic blending is required to ensure an effective, equitable and inclusive education for all.